Fermat's Last Theorem - Simon Singh (Fourth Estate, 1997)
The story of a puzzle that every child can understand but has baffled mathematicians for 300 years. Aged ten, Andrew Wiles stumbled across the puzzle, leading to a lifelong obsession with solving the world's greatest mathematical problem. A story of human endeavour and intellectual brilliance, for all readers. First published in 1997.